Deepfake Technology and Electoral Integrity: A Socio-Legal Analysis of Digital Manipulation and Democratic Rights in Indonesia - Nanda Pratama; Bilaly Sangare (Lembaga Publikasi Ilmiah Nusantara, 2026)
The rapid development of deepfake technology has generated significant challenges for electoral integrity, democratic legitimacy, and digital rights protection in Indonesia. During the 2024 Indonesian presidential election, the increasing circulation of AI-generated political content intensified concerns regarding disinformation, voter manipulation, and the weakening of public trust in democratic institutions. This study examines the socio-legal implications of deepfake technology in Indonesian electoral processes and evaluates the adequacy of existing legal frameworks in addressing AI-driven political manipulation. The research employs a qualitative socio-legal approach using statutory analysis, conceptual analysis, and thematic analysis of academic literature, legal instruments, and recent electoral developments. The findings demonstrate that Indonesian regulations, including the Electronic Information and Transactions Law and the Personal Data Protection Law, remain fragmented and insufficient to comprehensively regulate deepfake-based electoral disinformation. Deepfake dissemination during political campaigns creates substantial risks to democratic participation, electoral fairness, and informational integrity, particularly through social media amplification and algorithmic targeting. This article argues that Indonesia requires a specific and integrated regulatory framework combining electoral law reform, digital platform accountability, and AI governance mechanisms to protect democratic rights in the digital era. The study contributes to contemporary socio-legal debates concerning artificial intelligence, cyber democracy, and electoral governance in emerging democracies.